Numerical simulation of the skin tissue subjected to hyperthermia treatment using a nonlinear DPL model - Chaudhary R.K.; Kumar D.; Rai K.N.; Singh J. (My University, 2025)
This article deals with the study of simulation-based mathematical modeling of tissue using the non-linear dual-phase-lag bioheat transfer (DPLBHT) model for hyperthermia treatment of tumor or cancer cells with Gaussian distribution type heat source. The metabolic heat source as an exponential variation, blood perfusion rate as a linear variation and thermal conductivity as a linear variation are considered to be temperature-dependent, resulted in a more accurate prediction of the non-linear DPLBHT model. At initial time, τq is more effective than τt in the targeted region. When the infected or cancerous cells increases in width then for effective treatment the value of the antenna constant could be decreased and the value of probe region can be changed according to the tumor location in the skin tissue. When the value of γ, Wbo, a1 and a2 increases, the temperature profile in the target region decreases. The numerical solution is obtained by hybrid scheme using Runge Kutta (4,5) and finite difference technique. This technique is compared for accuracy with an exact analytical result in a particular case as shown in figures and table and found in good compliance. The effect of lagging, metabolic heat source, blood perfusion rate, coefficient of thermal conductivity, external heat source parameter and the other associated parameter are studied in detail and the results are presented graphically. © 2022 Elsevier Ltd